2008
DOI: 10.1111/j.1467-8551.2007.00546.x
|View full text |Cite
|
Sign up to set email alerts
|

Similarity, Isomorphism or Duality? Recent Survey Evidence on the Human Resource Management Policies of Multinational Corporations

Abstract: Copyright and moral rights to this work are retained by the author and/or other copyright owners unless otherwise stated. The work is supplied on the understanding that any use for commercial gain is strictly forbidden. A copy may be downloaded for personal, non-commercial, research or study without prior permission and without charge.Works, including theses and research projects, may not be reproduced in any format or medium, or extensive quotations taken from them, or their content changed in any way, withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
200
0
7

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(231 citation statements)
references
References 93 publications
(141 reference statements)
15
200
0
7
Order By: Relevance
“…Brewster, Wood, and Brookes (2008) found variations in a range of HR practices and concluded that multinational corporation tended to manage their human resources in ways that are distinct from those of their host country. Furthermore, Brewster, Wood, Brookes, and Van Ommeren (2006) showed that the HR component is affected not only by organizational size but also by sector and national location.…”
Section: Literature Review Hr Practices During Post-manda Integrationmentioning
confidence: 99%
“…Brewster, Wood, and Brookes (2008) found variations in a range of HR practices and concluded that multinational corporation tended to manage their human resources in ways that are distinct from those of their host country. Furthermore, Brewster, Wood, Brookes, and Van Ommeren (2006) showed that the HR component is affected not only by organizational size but also by sector and national location.…”
Section: Literature Review Hr Practices During Post-manda Integrationmentioning
confidence: 99%
“…These issues are typically researched through the survey method, often relying on one respondent per organisation (e.g. Rosenzweig and Nohria 1994;Brewster et al 2008). By contrast, this study draws on interviews with multiple key actors in each case study organisation, to provide a more multifaceted account of the array of perceptions and actions that inform decision-making processes entailed in managing the duality of pressures in practice.…”
Section: Research Approach and Casesmentioning
confidence: 99%
“…A significant amount of research on the HRM of MNCs has examined the degree of global integration or local responsiveness in subsidiary HRM practices by assessing whether a particular HRM practice or configuration of HRM practices resembles local practices, parent firm's practices or a hybrid of the two, and attempted to identify the contextual determinants of the balance (Björkman 2006;Rosenzweig 2006;Brewster et al 2008). However, insofar as our interest is in the issue of managing the dual pressures, it could be argued that this stream of research confronts two limitations.…”
Section: Managing the Duality In Hrm Of Mncsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pudelko and Harzing (2007) draw conclusions about the move towards dominant (US) practices based on analysis of 12 subjective, micro-focused, bipolar scale measures, covering recruitment, training, promotion, communication and employee incentives. Brewster et al (2008) focused on different HRM practices but the substantive areas of training, employee consultation, employee incentives and communication were employed. Our study also incorporated most of these substantive areas of HRM, as well as incorporating dimensions which have received limited attention to date.…”
Section: The Challenge Of Identifying Dominant/global Best Practicesmentioning
confidence: 99%